AI-driven MRI analysis reveals brain atrophy patterns in benign relapsing-remitting multiple sclerosis - M. Niiranen; M. Niiranen; P. Bendel; P. Bendel; J. Koikkalainen; J. Lötjönen; T. Selander; E. Solje; E. Solje; P. Hartikainen; S. Simula; R. Vanninen; et al. (Frontiers in Neurology)
BackgroundThe existence and definition of benign multiple sclerosis (MS) remain controversial, particularly given the discrepancy between clinical presentation and underlying imaging changes. In this study, we aimed to investigate the brain atrophy patterns related to benign relapsing-remitting MS (BRRMS), particularly regarding location and extent.MethodsWe analyzed global and regional gray matter (GM) and white matter (WM) volumes, WM lesion load, corpus callosum index (CCI) and corpus callosum area (CCA) in well-defined benign relapsing-remitting MS patients (BRRMS, n = 35) compared to healthy controls (HC, n = 35). Imaging data were analyzed using an AI-based volumetric analysis MRI (cNeuro®) and confirmed visually by an experienced neuroradiologist, ensuring robust validation.ResultsTotal brain tissue volume was significantly smaller in patients with BRRMS compared to HC (p < 0.001), but the cortical (p = 0.011) and cerebral (p = 0.002) GM volumes, as well as cingulate gyrus (p=0.032) and entorhinal area volumes (p < 0.001), were larger in BRRMS. GM volumes in the postcentral gyrus (p = 0.001), precentral gyrus (p < 0.001), the medial segment of the precentral gyrus (p < 0.001), supplementary motor cortex (p < 0.001) and thalamus (p < 0.001) were reduced in BRRMS compared to HC. Furthermore, both CCI and CCA were significantly smaller in BRRMS (p < 0.001 and p = 0.001, respectively).ConclusionsDespite the overall reduced brain volume compared to HC, distinct cortical regions, especially within the limbic system (i.e., cingulate gyrus and entorhinal area) GM may be relatively well preserved, indicating a possible compensatory volume increase. Based on this study, the corpus callosum is a crucial structure in monitoring disease progression in BRRMS.